Using "Show and Tell Games" in English Speaking Learning to Engage Secondary Students - Marisa Carolina; Fauzi Miftakh; Yousef Ahmad (Jurnal Ilmiah Wahana Pendidikan, 2022)
Abstract The purpose of this study was to determine how well students were engaging in games of "show and tell" when learning English. To collect the data and respond to the research questions that formed the foundation for this research, this study conducted a qualitative research with descriptive case study. At junior high school students from a 9th grade class, who were between the ages of 14 and 15 at the time of the research, were used as the sample, along with six other students. By observing students, the data for this study were gathered. A checklist of observations was used to get the instruments. In this study, the theory of Miles and Huberman was used to analyze the data. According to this theory, analysis consists of three flows of activity: data condensation, data display, and conclusion drawing/verification. Data analysis and evaluation of student engagement revealed that there was active and positive student interaction. This may be observable in the way they develop effective communication and self-confidence in front of the class, pay attention to their friends when they take turns explaining objects in front of the class, and grow more engaged about studying English. keywords: Speaking, Engagement, Show and Tell.